Serum Untargeted Metabolomics Reveal Potential Biomarkers of Progression of Diabetic Retinopathy in Asians - Wang, Zongyi; Tang, Jiyang; Jin, Enzhong; Zhong, Yusheng; Zhang, Linqi; Han, Xinyao; Liu, Jia; Cheng, Yong; Hou, Jing; Shi, Xuan; Qi, Huijun; Qian, Tong; et al. (Frontiers in Molecular Biosciences, 2022)
PURPOSE. To reveal molecular mechanisms of diabetic retinopathy (DR) in Asians and facilitate the identification of new therapeutic targets through untargeted metabolomics. To determine the differences in serum metabolites and metabolic pathways between different stages of diabetic retinopathy patients with Type 2 diabetic mellitus (T2DM), proliferative DR (PDR) and non-proliferative DR (NPDR)), and identify differential metabolites between T2DM and DR (NPDR and PDR) patients. METHODS. This prospective observational registration study described the differential metabolites between 45 T2DM patients and 15 control cases. Their biospecimens and clinical information were recorded. Serum metabolites were analyzed using high-resolution mass spectrometry with liquid chromatography. Untargeted metabolomics was performed on serum samples from 15 T2DM patients, 15 NPDR patients, 15 PDR patients, and 15 diabetic controls. RESULT. Trough untargeted metabolomics, 931 features (523 in positive and 408 in negative modes) with 102 common metabolites highly relevant to the presence of DR were detected. In the adjusted analysis, 67 metabolic features differed significantly between T2DM and NPDR patients. Pathway analysis revealed alterations in metabolisms of amino acids and fatty acid. Glutamate, phosphatidylcholine and 13-Hydroperoxyoctadeca-9,11-dienoic acid (13-PHODE) were key contributors to these pathway differences. A total of 171 features distinguished PDR patients from T2DM patients, and pathway analysis revealed alterations in amino acid metabolism, fatty acid metabolism, nitrogen metabolism and tricarboxylic acid cycle. Aspartate, glutamate, glutamine, ornithine, N-acetyl-L-glutamate, N-acetyl-L-aspartate, citrate, succinate, N-(L-arginino)succinate, 2-oxoglutarate, 13-PHODE, methionine, lysine, threonine, phenylalanine, N(pi)-methyl-L-histidine, phosphatidylcholine and linoleate were major contributors to the pathway differences. Between NPDR patients and PDR patients, there were 79 significant differential metabolites. Enrichment pathway analysis showed changes in amino acid metabolism, fatty acid metabolism, pantothenate and CoA biosynthesis. CONCLUSION. This study demonstrated the pathways of arginine biosynthesis metabolism, linoleic acid metabolism, alanine, aspartate and glutamate metabolism, as well as D-glutamine and D-glutamate metabolism were dysregulated in DR patients of Asian population. Increased levels of glutamate, aspartate, glutamine, N-acetyl-L-glutamate and N-acetyl-L-aspartate and decreased level of dihomo-gamma-linolenate, docosahexaenoic and icosapentaenoic were considered as the metabolic profile that could distinguish PDR from NPDR in Asians. Phosphatidylcholine and 13-PHODE were identified as two major novel metabolite markers in advanced stages of DR.